Anatomia e histologia do aparelho reprodutor e dados biológicos de Pomacea sp. (Mollusca, Gastropoda, Pilidae) - Mesquita, Eliana de Fátima Marques de (1982)
In this paper the author gives an anatomical and histological study of the reproductive system of Pomacea sp in order to obtain a rnorphological base to add to the knowledge of the features that we use in the specific identification of pilids. They give some general taxonomic considerations the geographical and geological distribution and a very short historical review of the genus. The author also studied the hard parts, that they considered as being shell, radula and jaw; and the soft parts, that is, the male and female reproductive system, and finally the biological data about the animal “in natura” and in the laboratory. The specimens were trapped in Jardim Botânico, Rio de Janeiro, and were taken to the laboratory where they grew up.